2016
DOI: 10.1093/ehjci/jew286
|View full text |Cite
|
Sign up to set email alerts
|

Heart mechanics at high altitude: 6 days on the top of Europe

Abstract: High-altitude exposure impaired LV diastolic function with the greatest effect observed at D2, concomitantly with the occurrence of AMS. The LV early filling impairments resulted from an increased RV afterload, a decrease in LV filling pressure and a delayed LV untwist. However, the increased LV twist probably acted as a compensatory mechanism to maintain cardiac performance during high-altitude hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 28 publications
8
74
0
1
Order By: Relevance
“…The LV CS, rotations and twist were obtained from short‐axis views according to specific recommendations (vanDalen, Vletter, Soliman, ten Cate, & Geleijnse, ). Analysis of LV strains and twist were conducted as previously described (Maufrais et al., , ; Nottin et al., ). Moreover, Echopac software includes an automatic detection of the subendocardial and subepicardial layers, allowing the assessment of the GLS and CS of the different layers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LV CS, rotations and twist were obtained from short‐axis views according to specific recommendations (vanDalen, Vletter, Soliman, ten Cate, & Geleijnse, ). Analysis of LV strains and twist were conducted as previously described (Maufrais et al., , ; Nottin et al., ). Moreover, Echopac software includes an automatic detection of the subendocardial and subepicardial layers, allowing the assessment of the GLS and CS of the different layers.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of untwist during isovolumic relaxation time (IVRT; %UT IVRT ) was calculated as follows (Zhang, Zhou, Pu, Zou, & Tan, ): %UT IVRT = [(twist at aortic valve closure − twist at the end of IVRT)/twist at aortic valve closure] × 100. The untwisting efficiency estimated through the untwisting rate/peak twist ratio as previously described was calculated as the peak untwisting velocity normalized for peak twist (Maufrais et al., ; Notomi et al., ). The TSR was calculated as peak twist divided by mean CS averaged from the basal and apical levels.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was considered that a reduction in plasma volume or a direct effect of hypoxia on LV myocardial contractility were probably responsible [ 4 ]. More recently it has been suggested that increased RV afterload may be of greater importance [ 5 ].…”
mentioning
confidence: 99%
“…Right ventricular systolic pressure (RVSP) was estimated from the peak velocity of the tricuspid regurgitation jet [ 1 , 5 , 7 9 ]. The LV and RV indices of myocardial performance (LIMP and RIMP) and tricuspid annular planar systolic excursion (TAPSE) were measured.…”
mentioning
confidence: 99%
“…It has been well documented that the global systolic left ventricular (LV) and right ventricular (RV) functions are well preserved, but both ventricles show altered filling patterns, subendocardial systolic dysfunction, and the increase in mean pulmonary arterial pressure (mPAP) [1][2][3]. Notably, there may be a potential association between altered cardiac functions and the incidence of acute mountain sickness [4], whereas the increase in mPAP may limit exercise capacity at HA [5,6]. Although the cardiac responses to HA exposure are of great significance, the detailed characterizations are largely unknown.…”
Section: Introductionmentioning
confidence: 99%